Профильный метод управления проектированием информационных систем организационного управления - Васильцова, Н. В.; Евланов, М. В.; Панфёрова, И. Ю.; Здор, Е. (My University, 2006)
Викладено результати аналізу особливостей застосування методології управління проектами для управління розробкою і впровадженням інформаційних систем організаційного управління. Запропоновано моделі основних профілів управління. Розглянуто ряд методів управління проектуванням і впровадженням інформаційної системи, заснованих на запропонованих моделях. The results of the analysis of the features of application of the methodology of project management for the management of the development and implementation of information systems of organizational management are described. Models of the main management profiles are proposed. A number of methods for managing the design and implementation of an information system based on the proposed models are considered.
Keywords: управление проектом; операционный профиль; профиль разработчика; профиль пользователя